FINANCIAL AND LEGAL ASPECTS OF THE ORGANIZATION OF THE AGRICULTURALLY USED AREAS MARKET - Hmyria Viktoriia Petrivna; Spirkina Oksana; Maksymenko Natalia; Tanklevska Nataliya (Scientific Journal of Pedagogy and Economics, 2019)
The article deals with the mechanism of functioning of the market of agriculturally used areas in Ukraine. The economic conditions of the formation of the land market that have developed in Ukraine determine the priority directions of economic contradictions in the formation of the land market. In addition, the article focuses on the regulatory and legal regulation of the agricultural land regime for the conducting farm-market agriculture, the farm and private farming, the analysis of changes envisaged by the Law of Ukraine “On Amendments to Certain Legislative Acts of Ukraine regarding the Solution of the Issue of Collective Land Ownership, Improvement of Land Tenure Rules of Agriculturally Used Areas, Prevention of Raiding and Stimulating the Irrigation in Ukraine” dated July 10, 2018, No. 2498-VIII.